Lixiviação de boro em latossolo em função de fontes e doses - Silva, Jefferson Ferreira da (2019)
Boron deficiency is the one that occurs most frequently among micronutrients, causing great losses of productivity in several crops in Brazil. However, the recommendations of their use in fertilization can not be disordered and without criteria. The objective of this work was to evaluate the potential of boron leaching as a function of doses and sources, as well as to determine the source with the lowest leaching potential and to evaluate leach losses at different doses in different soil layers. The experiment was installed in the experimental area of the State University of Goiás, Câmpus Ipameri. The experimental design was completely randomized, in a 3x5 factorial scheme, with four replications. The first factor consisted of boric acid, ulexite and H2 Boron sources, and the second factor was B (0; 12; 24; 36; and 48 kg ha-1). In the preparation of the experimental unit two PVC pipe rings 10 cm high each at the base and one 12 cm high at the top with 10 cm diameter were used. These rings were fixed to each other and filled to a height of 30 cm with a Latosol of medium texture collected in the superficial layer (0 to 40 cm). Soon after, a percolated irrigation water collection system was installed in the bottom of each soil column and the boron was applied to the surface of each soil column, with humidity close to the maximum water retention capacity. The comparison between the soil / leachate layer factors in each boron source and boron sources at each dose and at each layer was performed by applying the Kruskal-Wallis non-parametric test and the median test. In addition, for the dose factor of B, linear and polynomial regression analysis was performed. Regardless of the applied dose, the source ulexite is the one that presented the lowest content of soluble boron in the profile of the analyzed soils and also of leached liquid. Boric acid was the only source that had different behavior in relation to the content of boron in different layers of soil and leached material. In the 21 to 30 cm soil layer the ulexite is the source with the lowest content of leached boron. The behavior of the most soluble sources, in the case boric acid and H2 boron, regardless of the dose are very similar, being highly leachable in the profile of the Latosol used.